Sedimentation Management in the Brantas and Bengawan Solo Reservoir - Kodoatie, Robert; Rochim, Vianka; Lutfie Prananto, Thomasonan (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Sedimentation is a major issue in natural resource management in Indonesia, particularly in river basins with intense human activity such as the Brantas and Bengawan Solo. This phenomenon reduces reservoir storage capacity, shortens operational lifespan, and decreases hydropower efficiency. This study aims to evaluate sedimentation control strategies in these two critical river basins using a combination of quantitative and qualitative approaches. Field surveys and secondary data analysis revealed that the highest sedimentation rate in the Brantas Basin occurred in Wlingi Reservoir (5.359 tons/ha/year). In contrast, in the Bengawan Solo Basin, the highest rate was recorded in the Jeroan River (0.998 tons/ha/year). The erosion rates were also highest in Wonorejo (504.050 tons/ha/year) and Jeroan, respectively, indicating a strong correlation between erosion intensity and sediment yield. Several mitigation strategies were examined, including flushing, reservoir dredging, check dam dredging, and vegetative conservation. Among them, reservoir dredging and vegetative measures were the most effective. The study recommends future research on real-time sediment monitoring using IoT and AI-based sensors, optimization of vegetative conservation, and developing GIS-based hydrodynamic simulation models to support sustainable sediment management.